Forensic Analysis of Caffeine Content in Tea Samples using UV-Visible Spectroscopy - Anaida Santos (International Journal of Medical Toxicology and Legal Medicine, 2024)
Tea is widely used as a refreshing beverage to reduce fatigue, tiredness and create alertness. It contains caffeine that enhances the capacity of a person to work if consumed in a limited amount. However, in some cases, it is also used by athletes or by bodybuilders as supplement to enhance their workout potential and burn fat. Caffeine when consumed in combination with different drugs, narcotic substances and alcohol produces toxic symptoms that can lead to fatality. The objective of the present study is to determine and compare the caffeine concentration in 25 different brands of commonly available tea found in India using UV-visible spectroscopy. Caffeine was extracted from samples by liquid-liquid extraction method using chloroform as solvent. The concentration of caffeine in different tea samples ranged between 3.273 mg/g - 37.380 mg/g. It has been concluded that higher caffeine concentration in tea samples may produce toxic effects or even become fatal if taken in excess or in combination with other drugs. The technique UV-visible spectroscopy offers the advantage of being sensitive, reliable, accurate and economical for the analysis of caffeine concentration in tea samples.